Indicators of Motivation and Employee Satisfaction in Public Enterprise – Case Study of PE “Post of Serbia” - Urošević, Snežana; Milijić, Nenad; Đorđević Maljković, Nataša; Karabašević, Darjan (Industrija, 2016)
To motivate employees and create conditions for their satisfaction is one of the most important tasks of management aiming to create a successful organization. Employee satisfaction can lead to greater support of employees in achieving goals of the organization and creating a wider and larger market of products and services and higher profits. The paper’s objective was to examine key elements that influence satisfaction and motivation of the employees in public sector, i.e. in PE “Post of Serbia”. Public and private companies are different in material incentives which they provide to their employees, in fact public companies do not provide them, but are replaced by other factors of motivation and satisfaction, such as security. The paper also analyses the interactions between demographic factors-level of qualifications, years of work experience and age, on perception of satisfaction and motivation of employees as well as the consequences of these relations. Perception of satisfaction and motivation of employees is analyzed by using the responses of employees on questions divided into six groups: material conditions, safety, acceptance and social component, respect and status, self-confirmation and loyalty. The research uses the questionnaire methodology to collect data and it includes 31 questions regarding the satisfaction and motivation of the employees and demographic questions. The statistical analysis of the survey results provides the information on this area’s condition in Serbia, and first of all it points out the key elements of possible improvements. Instruments for collecting data used in this paper and data analysis gained in this way represent the very useful mechanism for helping the management to achieve better motivated and satisfied employees. To motivate employees and create conditions for their satisfaction is one on the most important tasks of management that wants to create a successful organization. Employee satisfaction can lead to greater support of employees in achieving goals of the organization and creating a wider and higher market of products and services and higher profits. The paper’s objective was to examine key elements that influence satisfaction and motivation of the employees in public sector. Public and private companies are different in material incentives which provide to their employees, in fact public companies do not provide, but are replaced by other factors of motivation and satisfaction, such as security. The research uses the questionnaire methodology to collect data and it includes 31 question regarding the satisfaction and motivation of the employees and demographic questions. The statistical analysis of the survey results provides the information on this area’s condition in Serbia, and first of all it points out the key elements of possible improvements. Instruments for collecting data used in this paper and data analysis gained in this way represent the very useful mechanism for helping the management to achieve better motivated and satisfied employees.